2019
DOI: 10.1111/ctr.13693
|View full text |Cite
|
Sign up to set email alerts
|

Donor hypernatremia and smoking addiction contribute to primary graft failure in heart transplantation

Abstract: Introduction: Primary graft failure (PGF) is an important contributor to early mortality, accounting for 41% of deaths within the first 30 days after heart transplantation (HT). Donor hypernatremia has been associated with PGF development. However, controversial data exist regarding the impact of sodium deregulation in patient survival after HT. This study aimed to assess the influence of donor hypernatremia on PGF development and to determine the serum sodium level threshold to assist in decision-making for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Although hypernatremia usually is defined by elevation of serum sodium to a concentration exceeding 145 mmol/L, 1,2 controversial data exists on the cut-off for clinically relevant hypernatremia, with values ranging from >145 to >169 mmol/L. [3][4][5]9,11 In the current study, the best discriminating sodium level regarding recipient mortality was above 156 mmol/L, with no additional significant change >159 mmol/L and a trend for >150 mmol/L. This goes in line with other studies investigating mortality and hypernatremia, for example in a small cohort of hospitalized hypernatremic patients in Switzerland.…”
Section: Cut-off Values For Relevant Donor Hypernatremiamentioning
confidence: 99%
See 1 more Smart Citation
“…Although hypernatremia usually is defined by elevation of serum sodium to a concentration exceeding 145 mmol/L, 1,2 controversial data exists on the cut-off for clinically relevant hypernatremia, with values ranging from >145 to >169 mmol/L. [3][4][5]9,11 In the current study, the best discriminating sodium level regarding recipient mortality was above 156 mmol/L, with no additional significant change >159 mmol/L and a trend for >150 mmol/L. This goes in line with other studies investigating mortality and hypernatremia, for example in a small cohort of hospitalized hypernatremic patients in Switzerland.…”
Section: Cut-off Values For Relevant Donor Hypernatremiamentioning
confidence: 99%
“…8 Regarding heart transplantation (HTx), Finger et al recently demonstrated in a single-center analysis in Brazil that serum sodium levels in donors above 159 mmol/L are associated with primary graft failure in recipients undergoing HTx. 9 So far, limited data is available on survival in heart transplant recipients regarding donor sodium levels. This study therefore aimed to first evaluate cut-off levels for donor hypernatremia and then investigate the impact of donor sodium levels on early morbidity and short-as well as midterm survival after HTx to support clinical decision-making in use of organs from hypernatremic donors.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the cut-off values for severity of hypernatremia range from >150 mmol/L [ 26 ] to >156 mmol/L [ 27 ]. Controversial and limited data exist regarding the impact of this donor sodium dysregulation in patient survival after solid organ transplantation, with cut-off levels for influence on survival ranging between 159 and 170 mmol/L [ 28 , 29 ]. Applying these cut-off levels to our cohort, those with a medium LOS in the ICU would be classified as mildly hypernatremic.…”
Section: Discussionmentioning
confidence: 99%
“…In general, cut-off values for hypernatremia severity range between >150 mmol/ [18] and >156 mmol/L [19]. There is controversial and limited data on the impact of donor sodium dysregulation on patient survival after solid organ transplantation, with cut-off values ranging from 159 to 170 mmol/L [20,21]. Therefore, in our cohort, those with high donor norepinephrine support have elevated but most likely not relevant mild hypernatremia without relevant influence on outcome or survival; however, this is limited obviously through the stated lack of data available on this topic.…”
Section: Discussionmentioning
confidence: 99%